1997
DOI: 10.1002/(sici)1096-8652(199706)55:2<59::aid-ajh2>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to activated protein C in unselected patients with arterial and venous thrombosis

Abstract: Four hundred and ninety-three consecutive patients referred for arterial or venous thrombosis were screened for congenital and acquired abnormalities of blood coagulation predisposing to thrombosis, and were compared to 341 age-and sex-matched controls. The aim of the study was to determine the prevalence and clinical characteristics of resistance to activated protein C (APC), a defect shown to have different prevalences in different ethnic groups and to be associated with an increased risk of thrombosis. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 29 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…A decreased response to activated protein C is common during pregnancy and during use of oral contraceptives, but the clinical relevance of these findings have yet to be determined [14]. Conditions associated with acquired protein C deficiency are DIC, deep venous thrombosis, pulmonary embolus, severe liver disease, postoperative patients, infection, malignancy, L-asparaginase therapy, ARDS, HUS and TTP [9,16]. Also, protein C levels may be decreased in postoperative patients, but the role of this decrease in contributing to or causing postoperative deep venous thrombosis is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…A decreased response to activated protein C is common during pregnancy and during use of oral contraceptives, but the clinical relevance of these findings have yet to be determined [14]. Conditions associated with acquired protein C deficiency are DIC, deep venous thrombosis, pulmonary embolus, severe liver disease, postoperative patients, infection, malignancy, L-asparaginase therapy, ARDS, HUS and TTP [9,16]. Also, protein C levels may be decreased in postoperative patients, but the role of this decrease in contributing to or causing postoperative deep venous thrombosis is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] It is present in a high number of Caucasians, 1,4,6,7,[10][11][12][13][14][15][16][17][18][19][20] but it is very rare in other ethnic groups. 7,17,[20][21][22][23][24][25] Few studies on Arabs showed that the prevalence of FVL was 0-27% in different Arabic countries, [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] being as low as zero in countries like Saudi Arabia, 7,29,40 Oman 34 and Yemen, 27 whereas being relatively very high (27%) in Palestinians (Israeli Arabs).…”
Section: Delta Rnmentioning
confidence: 99%
“…FVL was reported to be highly present in populations of Caucasian origin living in Europe, United States and Australia, with a prevalence of 15-65% among VTE patients and 1-15% in the normal populations studied. 1,4,6,7,[10][11][12][13][14][15][16][17][18][19][20] On the other hand, FVL was almost absent in other populations such as Africans, South-East Asians, Chinese, Japanese, American Indians, Greenland Eskimos and Aboriginals of Australia. 7,17,[20][21][22][23][24][25] In Kuwait, VTE is quite common.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations